Biogeochemical hotspots: temporal and spatial scaling of the impact of freshwater mussels on ecosystem function. (21st November 2014) - Atkinson, Carla L.; Vaughn, Caryn C.
Summary In streams, the creation of nutrient‐transformation hotspots by aggregated organisms may have heterogeneous and strong cumulative influences on stream nutrient dynamics. Here, we examine the potential for aggregations of freshwater mussels to create such hotspots. We measured nitrogen (N) and phosphorus (P) excretion rates of six mussel species and body tissue composition of eight. We combined these data with population densities of surveyed mussel beds in the Kiamichi River, OK, to estimate reach‐scale and stream‐scale nutrient recycling and storage. Additionally, we estimated the temporal variability in the magnitude of mussel nutrient recycling combining volumetric excretion at a reach scale with discharge and temperature data. Mussel beds constituted 1.45% of the area of the Kiamichi River. Mussel nutrient remineralisation varied greatly across beds (11.1–699.5 μmol N m−2 h−1 and 0.8–53.0 μmol P m−2 h−1), because of varying mussel densities. The community‐wide average excretion N:P (molar) of the mussel communities was 29.57, with higher excretion N:P significantly associated with higher abundances of Actinonaias ligamentina. Total nutrient storage per bed varied two orders of magnitude (6.3–631.7 kg N and 2.3–227.5 kg P) between mussel beds. Moreover, areal nutrient storage varied among the beds (11.2–133.7 mg N m−2, 4.1–48.9 mg P m−2) with the majority of nutrient storage in a long‐term store, shell (c. 87% of total N storage, c. 95% of total P storage). Freshwater mussels can be important to nutrient dynamics through nutrient regeneration and the creation of storage hotspots. However, the importance of nutrient remineralisation varies dramatically in response to organism patchiness, flow conditions and background nutrient concentrations.